Relationship between off-ice testing variables and on-ice speed in women's collegiate snchronized figure skaters: Implications for training - Bower, M. E.; Kraemer, W. J.; Potteiger, J. A.; Volek, J. S.; Hatfield, D. A.; Vingren, J. L.; Spiering, B. A.; Fragala, M. S.; Ho, J. -Y.; Thomas, G. A.; Earp, J. E.; Häkkinen, K.; et al. (The Journal of Strength and Conditioning Research, 2010)
The purpose of the current investigation was to identify any existing relationships between off-ice performance measures and on-ice performance quantified by speed and acceleration. Twenty-seven women (age 19 ± 1 year; body mass (59.5 ± 6.8 kg; height 164.6 ± 6.35 cm; body fat 23.2 ± 3.9%) who were collegiate synchronized figure skaters volunteered for the investigation. To examine the relationship between off-ice performance and on-ice speed and acceleration, collegiate synchronized skaters were evaluated on various performance tests over a 1-week period. Off-ice tests completed were peak torque for hip abduction and adduction, 40-yard sprint, vertical jump height, 30-second slide board stride count, and a 1-RM (repetition maximum) squat. On-ice tests included a timed single lap sprint, 4.5-minute (duration of long program) lap count, and an approximately 16.5-m (18-yard blue line to blue line) timed acceleration. Significance was set at P = 0.05. This study showed 3 primary findings: (a) slide board stride count was the single best predictor for both single lap on-ice speed and acceleration accounting for 53.5% (adjusted R2 value) of the variance in the single lap test and 42.5% (adjusted R2 value) of the variance in acceleration times; (b) vertical jump height test was the second best predictor for both the single lap test and on-ice acceleration accounting for 36.6% and 39.9% (adjusted R2 values) of the variance in times recorded, respectively; and (c) the best combined predictors for the single lap speed test were slide board stride count and 40-yard dash (R2 = 0.675), whereas the best combined predictors for on-ice acceleration were slide board stride count and vertical jump height test (R2 = 0.571). Conditioning for synchronized skaters to enhance performance of on-the-ice speed and acceleration should include slide board training implementation of plyometric and linear speed training while developing and maintaining 1-RM strength to support power capabilities.